Delayed Complex Spike Response Evoked by Conditioned Stimulus Encodes Movement Onset Time and Is Determined by Intrinsic Inferior Olive Properties - Yarden-Rabinowitz, Yasmin; Yarom, Yosef (Frontiers in Systems Neuroscience, 2019)
Recent studies demonstrate that after classical conditioning the conditioned stimulus (CS) triggers a delayed complex spike. This new finding revolutionizes our view on the role of complex spike activity. The classical view of complex spike as an error signal has been replaced by a signal that encodes for expectation, prediction and reward. In this brief perspective we review some of these works, focusing on the characteristic delay of the response (~ 80 msec), its independence on the time interval between CS and the unconditioned stimulus (US) and its relationship to movement onset. In view of these points we suggest that the generation of complex spike activity following learning, encodes for timing of movements onset. We then provide original data recorded from Purkinje and cerebellar nuclei neurons, demonstrating that delayed complex spike activity is an intrinsic property of the cerebellar circuit. We therefore suggest that learning of classical conditioning involves modulation of cerebellar circuitry where timing is provided by the inferior olive and the movement kinematic is delivered by the cerebellar nuclei projection neurons.